Interaction Mechanism of Inhibition of Palmitic Acid and α Selinene Targeting FabH and FabI Enzymes in Escherichia coli: In Silico Study - Tia Aulia; Nies Suci Suci Mulyani; Mukhammad Asy'ari (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Investigation studies of the interaction mechanism of palmitic acid and α-selinene in inhibiting FabH and FabI enzymes have been studied using an in silico approach. FabH (Beta-Ketoacyl-ACP Synthase III) and FabI (Enoyl-acyl carrier protein reductase) enzymes are two enzymes that are targets for the inhibition of candidate antibacterial compounds. This study aimed to determine the strongest candidate between palmitic acid and α-selinene as an antibacterial agent for Escherichia coli. The method used in this study is a random and directed molecular docking method using the Autodock Vina program, which is integrated into PyRx 0.8 software. The results of the molecular docking simulation include the pattern and strength of interaction between the ligand and the FabI and FabH enzymes. The interaction pattern includes the cluster pattern, the ligand poses on the protein surface, and the interaction strength based on the binding affinity value. Based on the results of random docking simulation data analysis, it was shown that the majority of α-selinene occupied the position of cluster 1 of the FabI enzyme and palmitic acid in cluster 2 of the FabH enzyme. Based on the binding affinity value, palmitic acid has a weaker interaction strength on the FabH enzyme (-5.7 kcal/mol) than on the FabI enzyme (-7.1 kcal/mol). The interaction strength of α-selinene on the FabI enzyme (-7.3 kcal/mol) was stronger than that of the FabH enzyme (-6.9 kcal/mol). The interaction strength of α-selinene in both FabI and FabH enzymes was greater than that of palmitic acid. α-selinene is projected to have a better potential as an antibacterial agent against Escherichia coli than palmitic acid based on its greater interaction strength.